The Market of Civic Aviation in Russia: Formal and Informal Interactions of Actors - Наталия Ивановна Скрыльникова (Journal of Economic Sociology, 2010)
The goal of the study is to analyze informal interactions of actors on the market of civic aviation in Russia linking them to the formal relations. The object of the study is the representatives of main types of market actors in Russian civic aviation. The subject of the research is the formal and informal interactions between main participants of the civic aviation market in Russia as well as the relation inside the companies of this market.